A fully automated image analysis framework for quantitative assessment of temporal tumor changes - Emmanouilidou, Dimitra (E-Health and Bioengineering Conference, 2011)
This paper presents a novel framework for assessing tumor changes based on histogram analysis of temporal Magnetic Resonance Image (MRI) data. The proposed method detects the distribution of tumor and quantitatively models its growth or shrinkage offering the potential to assist clinicians in objectively assessing subtle changes during therapy. The presented work and the initial validation refer to the glioma case but can be generalized to any type of cancer where medical imaging is routinely used to characterize tumor response over time.